2017
DOI: 10.1371/journal.pone.0177722
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in relationship between serum ferritin and 25-hydroxyvitamin D in Korean adults

Abstract: BackgroundThe present study was conducted to assess the gender difference in the relationship between serum ferritin and 25-hydroxyvitamin D [25(OH)D] in Korean adults.MethodsA total of 5,147 adults (2,162 men, 1,563 premenopausal women, and 1,422 postmenopausal women) aged ≥ 20 years from the Korean National Health and Nutrition Examination Survey (KNHANES) data (2012) were analyzed. A covariance test adjusted for covariates was performed for serum ferritin levels in relation to vitamin D status (vitamin D de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…Our cohort consisted of mostly middle aged Asians with higher socioeconomic and education levels and urban habitation with the highest annual PM concentrations in the world. Thus, these characteristics can contribute to more increase in the amount of mobilized iron especially in men than women in our cohort [8,[21][22][23][24][25][26]. The large difference in serum ferritin level between men and women can contribute to much higher lifetime iron stores in men than in women.…”
Section: Study Design and Populationmentioning
confidence: 82%
“…Our cohort consisted of mostly middle aged Asians with higher socioeconomic and education levels and urban habitation with the highest annual PM concentrations in the world. Thus, these characteristics can contribute to more increase in the amount of mobilized iron especially in men than women in our cohort [8,[21][22][23][24][25][26]. The large difference in serum ferritin level between men and women can contribute to much higher lifetime iron stores in men than in women.…”
Section: Study Design and Populationmentioning
confidence: 82%
“…None of the above studies had considered potential confounders in the association of vitamin D with SF. A recent analysis of the Korea National Health and Nutrition Survey did consider confounders and reported an inverse association between serum 25(OH)D and SF among Korean men [29]. The authors also reported this association for premenopausal women [29] and for women without metabolic syndrome [28], but not for post-menopausal women [29] and women with metabolic syndrome [28].…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of the Korea National Health and Nutrition Survey did consider confounders and reported an inverse association between serum 25(OH)D and SF among Korean men [29]. The authors also reported this association for premenopausal women [29] and for women without metabolic syndrome [28], but not for post-menopausal women [29] and women with metabolic syndrome [28]. The latter, to some extent, seems consistent with the observation of the present study that an association between vitamin D and SF was observed among under/normal weight Canadians, but not among those with overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the potential influence of vitamin D on SF concentrations, as an inflammation marker, has received relatively little attention. Conclusions from existing and mostly cross-sectional studies are inconsistent [2,17,18,19,20,21,22,23]. Therefore, the objective of this study is to shed more light on the cross-sectional associations of serum 25-hydroxyvitamin D (25(OH)D) with SF concentrations, and, importantly, to examine whether temporal increases in serum 25(OH)D concentrations are paralleled by the reduction in the SF concentrations.…”
Section: Introductionmentioning
confidence: 99%